Doorway of John F.X. Ritchie's Hotel, Evandale, Tasmania, ca. 1970 - Stacey, Wes (Wesley), 1941-2023. (1968)
Depicting doorway, Foster's Lager sign, pilastered columns, door panels.
Part of the Wes Stacey archive of architectural photographs, 1968-1972.
Catalogue record generated as part of a batch load.
Title from acquisitions document, see file NLA09/703.
Wes Stacey reference number: 5 52 7.
Also available online
Keywords: Hotels -- Tasmania -- Evandale -- Photographs; Doorways -- Tasmania -- Evandale -- Photographs; Evandale (Tas.) -- Buildings, structures, etc. -- Photographs